2003
DOI: 10.4049/jimmunol.171.2.955
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Hyperoxia Impairs Pulmonary Innate Immunity

Abstract: Supplemental oxygen is often required in the treatment of critically ill patients. The impact of hyperoxia on pulmonary host defense is not well-established. We hypothesized that hyperoxia directly impairs pulmonary host defense, beyond effects on alveolar wall barrier function. C57BL/6 mice were kept in an atmosphere of >95% O2 for 4 days followed by return to room air. This exposure does not lead to mortality in mice subsequently returned to room air. Mice kept in room air served as controls. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 58 publications
5
108
3
Order By: Relevance
“…Several studies have suggested that hyperoxia impairs pulmonary immunity and increases the risk of invasive pulmonary infection. Baleeiro and associates found that mice exposed to hyperoxia had increased mortality associated with gram-negative bacterial pneumonia compared to mice exposed to RA [4]. An increased bacterial burden and dissemination of the infection was also noted at the time of autopsy in the mice exposed to hyperoxia [4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have suggested that hyperoxia impairs pulmonary immunity and increases the risk of invasive pulmonary infection. Baleeiro and associates found that mice exposed to hyperoxia had increased mortality associated with gram-negative bacterial pneumonia compared to mice exposed to RA [4]. An increased bacterial burden and dissemination of the infection was also noted at the time of autopsy in the mice exposed to hyperoxia [4].…”
Section: Discussionmentioning
confidence: 93%
“…Bacterial adherence leading to colonization is the first step in the process of invasive pulmonary infection, with phagocytosis by alveolar macrophages critically important in preventing invasive pulmonary infection. Several studies have suggested that hyperoxia impairs pulmonary immunity and increases the risk of invasive pulmonary infection in newborn animal models and preterm infants (2)(3)(4)(5)(6). In fact, the STOP-ROP study suggested that preterm infants receiving higher inspired oxygen concentrations had an increased incidence of pneumonia and BPD, although the study was not designed to specifically examine this outcome [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it may be that BMT AMs are defective due to the persistent lack of supportive factors from structural/resident cells within the BMT lung. It is possible that the conditioning regimen (irradiation) alters the ability of the pulmonary parenchymal cells, especially alveolar epithelial cells, to support AM differentiation in the lung (36).…”
Section: Discussionmentioning
confidence: 99%
“…Different lung disease models such as asthma and more recently hyperoxia-induced lung injury could be linked to NKT cell-induced immune responses [1,[3][4][5][6][7]. Hyperoxia remains a mainstay in clinical patient care in order to improve oxygen delivery to crucial organs in critically ill patients suffering from acute lung injury or during cardiac surgery to name a few [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoxic lung injury is typically characterized by alveolar epithelial as well as endothelial damage. These effects result in a capillary leak syndrome followed by inflammatory cell recruitment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%